(untitled) (Revista Nacional de Odontología, 2017)
Introduction: Adequate diagnosis of dentoalveolar discrepancy and early treatment is key to prevent occlusal and dento-osseous alterations that complicate future treatments in permanent dentitions. The present research seeks to determine the effectiveness of new simplified formulas for the design and assessment of predictive analysis in mixed dentition dento-osseus discrepancy in children between 7 and 10 years old treated at the Hospital Universitario Metropolitano de Barranquilla. Method: Correlational descriptive study in study models of children between 7 and 10 years old who were treated at the Fundación Hospital Universitario Metropolitano between 2012 and 2013. Randomized probability sampling was used; after calculating the sample size with a 95 % confidence interval and a margin of error of 5 %, a sample of 119 children was obtained. A pilot test was carried out with 27 % of the total population in order to make relevant adjustments. Results: The discrepancies obtained in the results of simplified formulas yielded findings significantly similar to the values obtained by Moyers, thus providing an accurate diagnosis of malocclusions. The measurements of canine tooth size and the measurements of the space required for the eruption of premolars were similar in terms of mean and standard deviation. Conclusion: The equations resulting from this research will be used as a tool for the predictive analysis in mixed dentition in the Colombian population of Barranquilla.